Statistical study of traveling ionospheric disturbances over South Africa - Mahlangu, Daniel Fiso (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2019)
This thesis provides a statistical analysis of traveling ionospheric disturbances (TIDs) in South Africa. The velocities of the TIDs were determined from total electron content (TEC) maps using particle image velocimetry (PIV). The periods were determined using Morlet function in wavelet analysis. The TIDs were grouped into four categories: daytime, twilight, nighttime TIDs, and those TIDs that occurred during magnetic storms. It was found that daytime medium scale TIDs (MSTIDs) propagated equatorward in all seasons (summer, autumn, winter, and spring), with velocities of about 114 to 213 m/s. Their maximum occurrence was in winter between 15:00 and 16:00 LT. The daytime large scale (TIDs) LSTIDs propagated equatorward with velocities of approximately 455 to 767 m/s. Their highest occurrence was in summer, between 12:00-13:00 LT. Most of the these TIDs (about 78%) were observed during the passing of the morning solar terminator. This implied that the morning terminator was more effective in instigating TIDs. Only a few nighttime TIDs were observed and therefore their behavior could not be statistically inferred. The TIDs that occurred during magnetically disturbed conditions propagated equatorward. This indicated that their source mechanism was atmospheric gravity waves generated at the onset of geomagnetic storms.
Keywords: Ionosphere -- Research; Sudden ionospheric disturbances; Gravity waves; Magnetic storms